Sosialisasi Mitigasi Bencana Banjir dengan Melibatkan Peran Serta Masyarakat di Pesisir Danau Tempe Kabupaten Wajo - Mukti Ali; Sri Aliah Ekawati; Ariuddin Akil; Mimi Arifin; Ihsan Ihsan; Wiwik Wahidah Osman; Yashinta K. Dewi; Abdul Rachman; Isfa Sastrawati; Marly Valenti P; Venny Veronica N; Laode Muh. Asfan Mujahid; Gafar Lakatupa; Sri Wahyuni; Jayanti Mandasari; Suci Anugrah Yanti; Dewa Sagita Alfadin N; Muh. Fachrul Razy; Masfirah Sriwulandari (Faculty of Engineering UNHAS, 2023)
The coastal of Lake Tempe is located in Watallipue Village, Wajo Regency, which is one of the flood-prone residential areas. The flood disaster that occurred in the coastal area of Lake Tempe caused various problems to arise both from physical and non-physical aspects. Flooding in Watallipue Village occurs almost every year due to the overflow of Lake Tempe and surrounding rivers with heights ranging from 1m to 5m. Based on field observations, 100% of the coastal communities of Lake Tempe have been affected by floods. At the time of the flood, people living in a radius of 50-100m from the river bank were evacuated to a safe place because the flood reached a height of 5-6m. The purpose of this community service activity is to socialize flood disaster mitigation by involving community participation. The implementation method is in the form of community service. Data collection techniques are observation, documentation and interviews. The data analysis techniques are descriptive qualitative and spatial. As a first step, interviews and questionnaires were distributed to 56 respondents to determine the level of understanding of flood mitigation. Initial interviews showed only 23 of the 56 communities knew of the efforts that could be made in mitigating the impact of flooding. In addition, there are only 12 people who know the importance of signs, evacuation routes and temporary evacuation sites. Based on these conditions, socialization was carried out in the form of FGDs related to the concept of disaster mitigation by involving the community. The form of implementation of this concept is that the community plays a role in determining evacuation routes during floods, determining evacuation points in the area around the residence and compiling efforts to reduce the risk of flooding in the coastal area of Lake Tempe. The community conveyed that they were active in discussions and had high hopes for the government's assistance in efforts to mitigate flood disasters on the shores of Lake Tempe. The results of this activity show an increase in public understanding of flood mitigation. The post-test results showed that 56 respondents (100%) understood the efforts that can be made in reducing the impact of flood disasters and the importance of providing signs, evacuation routes and temporary evacuation sites.